Perlindungan Hukum bagi Pers dalam Melaksanakan Kebebasan Pers di Indonesia dan Australia - Trisnaningrum, Roshita Anggun; Kartika, Adhitya Widya (Jurnal Hukum & Pembangunan, 2024)
The press and democratic life are two inseparable things. The existence of the press has a crucial role in conveying information, providing education to the public, and as a means of social control. Freedom of the press is not only recognized internationally, but every country is obliged to provide legal protection for it. The urgency of this research from a constitutional law perspective is that the press is the fourth pillar of democracy (the fourth of estate). This issue is discussed to discover the similarities and differences in press law provisions between Indonesia and Australia as well as to improve, update, or find answers to press law problems. This research applied normative methods with comparative, statutory, and conceptual approaches, as well as qualitative analysis. There are two aspects analyzed in this research, the first regarding the comparison of legal provisions regarding press freedom in Indonesia and Australia based on press system theory and the second regarding good positive legal benchmarks in providing legal protection for the press in Indonesia and Australia. The results of this research are that Indonesian press law provisions have protected press freedom compared to Australian press law provisions which tend not to protect press freedom and Indonesian positive law has fulfilled the elements of legal protection compared to Australian positive law which tends not to have fulfilled the elements of legal protection. Keywords: Press Freedom, Legal Protection, Comparison, Indonesia, Australia.